Renal failure due to renal vein thrombosis in a fetus with growth restriction and thrombophilia. Issue 4 (26th February 2014) - Has, Recep; Corbacioglu Esmer, Aytul; Kalelioglu, Ibrahim H.; Yumru, Harika; Yüksel, Atil; Ziylan, Orhan
Abstract We report a case of renal vein thrombosis diagnosed at 27 weeks of gestation in a dichorionic twin pregnancy. The left kidney of one fetus was hyperechoic and enlarged with echoic streaks following the direction of interlobular veins and the loss of corticomedullary differentiation. In the following weeks, left kidney became smaller and echoic, and Doppler examination showed no flow in both artery and vein. The right kidney had totally normal appearance in the beginning, but it became enlarged and hyperechoic, and progressed into a small echoic kidney with no flow in artery and vein. In the postnatal ultrasound examination, both kidneys appeared hyperechoic with no vascularization in the hilum region. There was thrombosis in arteries and veins of both kidneys, as well as in the inferior vena cava. The investigation for thrombophilia resulted with the combined presence of heterozygote mutation in factor V Leiden and prothrombin 20210 genes.